Implementation of telerehabilitation in Austrian outpatient physiotherapy - A qualitative study / Implementierung von Telerehabilitation in der ambulanten Physiotherapie in Österreich - Eine qualitative Studie - Guggenberger Bernhard; Jocham Birgit; Maul Lukas; Jocham Andreas J. (Sciendo, 2022)
New technologies, for example, telerehabilitation (TR) tools, can support physiotherapists' work. Even though studies have demonstrated their potential, TR is not yet fully implemented in Austrian outpatient physiotherapy. As a result of the Coronavirus pandemic and the associated lockdowns, physiotherapists in Austria were confronted with the challenge of offering therapies without physical contact. This study aims to investigate opinions and experiences of physiotherapists in Austria regarding TR and its implementation in different clinical fields.